History of Economic Thought, Methodology, and Heterodox Approaches: Worldly Philosopher: The Odyssey of Albert O. Hirschman - McPherson, Michael (Journal of Economic Literature, 2013)
Michael McPherson of The Spencer Foundation reviews, “Worldly Philosopher: The Odyssey of Albert O. Hirschman” by Jeremy Adelman. The Econlit abstract of this book begins: “Explores the life and economic work of Albert O. Hirschman. Discusses Hirschman's early life in the Weimar Republic; Hirschman's education and early relationship with politics; Hirschman's journey to Paris; Hirschman's move to the London School of Economics and involvement in the Spanish Civil War; Hirschman's return to France and the outbreak of World War II; Hirschman's emigration to the United States; Hirschman's involvement in the U.S. Army; the aftermath of World War II; the Cold War and Red Scare; Hirschman's years in Colombia; Hirschman's Yale University years and The Strategy of Economic Development; the RAND Corporation; travel and research; the upheaval of the late 1960s; crisis and hope in Latin America; Hirschman and the Institute for Advanced Study; Hirschman's relationship with the human body; Hirschman during the late 1970s and early 1980s; Hirschman's study of the ethics of social science; Hirschman's work in retirement; and Hirschman's final years. Adelman is Walter Samuel Carpenter III Professor of Spanish Civilization and Culture and Director of the Council for International Teaching and Research at Princeton University.”